The Effect of Inflation Rate and Gold Price on Gold Pawn Financing (Rahn) at PT Bank BSI Indonesia - Melda Kusuma Wardani; Norita Citra Yuliarti; Riyanto Setiawan Suharsono (Westscience Press, 2024)
Gold pawn financing can be interpreted as pawning or surrendering physical authority over property/valuables from customers to banks to be managed with the ar-rahn principle, namely as collateral for loans/debts given to customers/borrowers. The purpose of this study was to determine the effect of inflation rate and gold price on the distribution of Rahn financing at PT Bank Syariah Indonesia. The data for this research comes from the official website of Bank Indonesia, PT Antam Indonesia and PT Bank Syariah Indonesia. The data taken is a monthly report. Hypothesis testing using multiple linear regression analysis and data processing tools with the SPSS 21 application. The results of data analysis show that partially the inflation rate does not have a significant effect on the distribution of Rahn Financing of PT Bank Syariah Indonesia with a t value of -2.03 and a significant value of 0.051, and gold price fluctuations affect the distribution of Rahn Financing of PT Bank Syariah Indonesia with a t value of 7.811 and a significant value of 0.000. Simultaneously the inflation rate and gold price affect the distribution of Rahn Financing of PT Bank Syariah Indonesia with an F value of 30.81 and a significance of 0.000 and can be seen from the regression coefficient test (R2) the inflation rate and gold price fluctuations affect the distribution of Rahn Financing of PT Bank Syariah Indonesia by 64.4% and the remaining 35.6% is influenced by other factors outside the research model.